Be Water by Antía Yáñez and Plop by Rafael Pinedo as Dystopian Allegories of Capitalism - Pietrak, Mariola (Madrygal. Revista de Estudios Gallegos, 2023)
The texts of the two decades of the 21st century give an account of the deep malaise that (late) capitalistic societies experience. Through channels such as dystopia or paroxysm, they denounce the increasingly oppressive mechanisms of the well-known systems, paradoxically, such as the ‘government of the people’: democracies. This study proposes an approach to two novels –Be Water (2019) by Antía Yáñez and Plop (2002) by Rafael Pinedo– which, as it is to be argued, constitute dystopian allegories of our current capitalistic reality. Coming from two different latitudes, they reveal the global scope of the abuses of capitalism and the vulnerability of individuals in socio-political structures dependent on the implacable laws of the market. The abovementioned abuses and vulnerability intensify in times of crisis, such as the Argenitian one in 2001 and the Spanish one in 2008 (and their previous moments), or in the so-called third world regions, reaching dystopian dimensions.